Sacred music - the meeting between the divine and the human according to the Holy Scriptures - Damian, Lucian (Technium Social Sciences Journal, 2022)
Man is by definition the creature created by God to be in communion with Him, to share in the eternity of the Creator, and sacred music has the ability to reduce the distance between God and man, raising the latter to an experience special prayer, the experience through which man speaks directly to his Creator.